Queer(y)ing public administration - Lee, Hugh; Harding, Nancy; Learmonth, Mark (2008)
Queer theory, understood here as a set of political/politicized practices and positions which resist normative knowledge and identities, has emerged as a theoretical perspective having important emancipatory and explanatory power in the arts, humanities and social sciences. Queer theory resists definition ipso facto, residing as it does within a postructuralist paradigm. It has not hitherto featured within the discipline of public administration and we argue the case for its utilisation in this field by first explicating the theory. Here we develop a way of using queer theory to analysis data, notably through the identification of the `moments' of a queer theory analysis: identification of the norms that govern identity, analysis of what is allowable within those norms, and exploration of what is unspeakable. We demonstrate its use via an empirically-based case study. The lessons from this exercise are then applied to some of our earlier work which we re-read through a queer theory lens. This shows the great explanatory power offered by the theory, in that it can develop insights that previously have been inaccessible. We conclude with recommendations for its broader application and wider use within public administration. - Reproduced.
Keywords: Public administration